2018
DOI: 10.1083/jcb.201605106
|View full text |Cite
|
Sign up to set email alerts
|

An ordered pattern of Ana2 phosphorylation by Plk4 is required for centriole assembly

Abstract: Centriole duplication is tightly regulated throughout the cell cycle to ensure one duplication event per centriole. McLamarrah et al. show that a stepwise pattern of Ana2 phosphorylation by Plk4 facilitates proper centriole duplication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 53 publications
4
62
1
Order By: Relevance
“…Drosophila Ana2 does not require direct binding to Plk4 for its recruitment to procentrioles (McLamarrah et al, 2018). However, centriole recruitment of Ana2/STIL does require Plk4 kinase activity as well as phosphorylation of Ana2’s N terminus (Moyer et al, 2015; Dzhindzhev et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Drosophila Ana2 does not require direct binding to Plk4 for its recruitment to procentrioles (McLamarrah et al, 2018). However, centriole recruitment of Ana2/STIL does require Plk4 kinase activity as well as phosphorylation of Ana2’s N terminus (Moyer et al, 2015; Dzhindzhev et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the finding that deletion of the central coiled-coil in Ana2 prevents Plk4 binding and targeting to centrioles (Ohta et al, 2014; Arquint et al, 2015; Kratz et al, 2015; Moyer et al, 2015), it has been proposed that a direct interaction with Plk4 mediates Ana2 loading onto centrioles. However, we have shown that coiled-coil deletion actually has multiple deleterious effects because it also disrupts Ana2’s ability to oligomerize and interact with Sas4 (McLamarrah et al, 2018). By using a separation-of-function phosphomimetic (PM) mutation in Ana2 that is unable to bind Plk4, we observed that PM Ana2 localizes properly to the procentriole assembly site (McLamarrah et al, 2018), suggesting that Ana2 recruitment relies on a mechanism independent of Plk4 binding.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations